1-nonene plays an important role in the response of maize-aphid-ladybird tritrophic interactions to nitrogen - Zhao, Shi-Wen; Pan, Yu; Wang, Zhun; Wang, Xiao; Wang, Shang; Xi, Jing-Hui (Frontiers in Plant Science, 2024)
Plant volatile organic compounds (VOCs) are the key distress signals involved in tritrophic interactions, by which plants recruit predators to protect themselves from herbivores. However, the effect of nitrogen fertilization on VOCs that mediate tritrophic interactions remains largely unidentified. In this study, a maize (Zea mays)-aphid (Rhopalosiphum padi)-ladybird (Harmonia axyridis) tritrophic interaction model was constructed under high-nitrogen (HN) and low-nitrogen (LN) regimens. H. axyridis had a stronger tendency to be attracted by aphid-infested maize under HN conditions. Then, volatiles were collected and identified from maize leaves on which aphids had fed. All of the HN-induced volatiles (HNIVs) elicited an electroantennogram (EAG) response from H. axyridis. Of these HNIVs, 1-nonene was attractive to H. axyridis under simulated natural volatilization. Furthermore, our regression showed that the release of 1-nonene was positively correlated with H. axyridis visitation rates. Supplying 1-nonene to maize on which aphids had fed under LN enhanced attractiveness to H. axyridis. These results supported the conclusion that 1-nonene was the active compound that mediated the response to nitrogen in the tritrophic interaction. In addition, the 1-nonene synthesis pathway was hypothesized, and we found that the release of 1-nonene might be related to the presence of salicylic acid (SA) and abscisic acid (ABA). This research contributes to the development of novel environmentally friendly strategies to optimize nitrogen fertilizer application and to improve pest control in maize crops.